Convergence of distributions of integral functionals of extremal random functions - Matsak, I. K. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We study the convergence of distributions of integral functionals of random processes of the formU n (t)=b n (Z n (t)-a n G(t)),t⃛T, where {X=X(t), t⃛T} is a random process,X n ,n≥1, are independent copies ofX, andZ n (t)=max1≤k≤n X k (t).